Changing Gender Norms across Generations: Evidence from a Paternity Leave Reform - Lídia Farré; Christina Felfe; Libertad Gonzalez; Patrick Schneider (Institute of Labor Economics (IZA), 2023)
Social norms are an important barrier to gender convergence. We show that public policy designed to promote gender equality at home can pave the way towards gender convergence by shaping gender norms in the next generation. We combine the introduction of paternity leave in Spain with a large-scale lab-in-the field experiment in secondary schools. Following a local difference-in-differences approach, we show that children born after the policy change exhibit more gender egalitarian attitudes and perceive less stereotypical social norms. They are also more likely to engage in counter-stereotypical day-to-day behaviors and to deviate from the male-breadwinner model in the future.
Keywords: J08; J13; J16; J18; 330; gender equality; gender norms; paternity leave permits